Promoter Sequence of Shiga Toxin 2 (Stx2) Is Recognized In Vivo, Leading to Production of Biologically Active Stx2 - Leticia V. Bentancor (American Society for Microbiology, 2013)
ABSTRACT Shiga toxins (Stx) are the main agent responsible for the development of hemolytic-uremic syndrome (HUS), the most severe and life-threatening systemic complication of infection with enterohemorrhagic Escherichia coli (EHEC) strains. We previously described Stx2 expression by eukaryotic cells after they were transfected in vitro with the stx2 gene cloned into a prokaryotic plasmid (pStx2). The aim of this study was to evaluate whether mammalian cells were also able to express Stx2 in vivo after pStx2 injection. Mice were inoculated by hydrodynamics-based transfection (HBT) with pStx2. We studied the survival, percentage of polymorphonuclear leukocytes in plasma, plasma urea levels, and histology of the kidneys and the brains of mice. Mice displayed a lethal dose-related response to pStx2. Stx2 mRNA was recovered from the liver, and Stx2 cytotoxic activity was observed in plasma of mice injected with pStx2. Stx2 was detected by immunofluorescence in the brains of mice inoculated with pStx2, and markers of central nervous system (CNS) damage were observed, including increased expression of glial fibrillary acidic protein (GFAP) and fragmentation of NeuN in neurons. Moreover, anti-Stx2B-immunized mice were protected against pStx2 inoculation. Our results show that Stx2 is expressed in vivo from the wild stx2 gene, reproducing pathogenic damage induced by purified Stx2 or secondary to EHEC infection. IMPORTANCE Enterohemorrhagic Shiga toxin (Stx)-producing Escherichia coli (EHEC) infections are a serious public health problem, and Stx is the main pathogenic agent associated with typical hemolytic-uremic syndrome (HUS). In contrast to the detailed information describing the molecular basis for EHEC adherence to epithelial cells, very little is known about how Stx is released from bacteria in the gut, reaching its target tissues, mainly the kidney and central nervous system (CNS). In order to develop an efficient treatment for EHEC infections, it is necessary to understand the mechanisms involved in Stx expression. In this regard, the present study demonstrates that mammals can synthesize biologically active Stx using the natural promoter associated with the Stx-converting bacteriophage genome. These results could impact the comprehension of EHEC HUS, since local eukaryotic cells transduced and/or infected by bacteriophage encoding Stx2 could be an alternative source of Stx production.